Ethnobotany for Beginners - a review - Malik, Zubair Ahmed (Ethnobotany Research and Applications, 2020)
Ethnobotany for Beginners. Ulysses Paulino Albuquerque, Marcelo Alves Ramos, Washington Soares Ferreira Júnior, Patrícia Muniz de Medeiros. Springer, Cham, Switzerland 2017. xii + 71 pp. (paperback). Price: € 57.19, ISBN 978-3-319-52871-7. doi: 10.1007/978-3-319-52872-4 Are you a beginner of Ethnobotany Research? If ‘YES’, I want to recommend to you a very useful, reliable, and a valuable guide for the research in this discipline and that is a booklet “Ethnobotany for Beginners” by Albuquerque et al (2017). This booklet is a part of book series, Springer Briefs in Plant Science (Volume 16). Twenty-five volumes of this book series have been published since 2012 till now (September 2020). The book under review (Ethnobotany for Beginners) is the translation from the Portuguese language edition: Introdução a Etnobotânica (Introduction to Ethnobotany) by Ulysses Paulino de Albuquerque that was published in 2005. With just 71 pages, written by the authors well recognized in the field of ethnobotany and forwarded by Prof. Julio Alberto Hurrell of National University of La Plata (UNLP) Argentina, the booklet is especially designed for the beginners that features a quick and easy-to-read discussion of ethnobotany along with its major developments. In the foreword, Prof. Hurrell says, “the accessible language of this book brings ethnobotany closer to a broad and diverse audience consisting of academics as well as the layman and acts as an effective incentive for students who see in this science an interesting opportunity for their future professional development”. As the title (Ethnobotany for Beginners) suggests, the book has been prepared especially for the those who are learners, beginners and/or new to the field of ethnobotany and interested in a quick and pleasant read containing an overview of ethnobotany and its major developments. The booklet fills the gap of an introductory text that aims to prepare the reader for denser and complex readings of the topic.